2001
DOI: 10.1016/s0002-9440(10)61722-1
|View full text |Cite
|
Sign up to set email alerts
|

The Perifollicular and Marginal Zones of the Human Splenic White Pulp

Abstract: We investigate the white pulp compartments of 73 human spleens and demonstrate that there are several microanatomical peculiarities in man that do not occur in rats or mice. Humans lack a marginal sinus separating the marginal zone (MZ) from the follicles or the follicular mantle zone. The MZ is divided into an inner and an outer compartment by a special type of fibroblasts. An additional compartment, termed the perifollicular zone, is present between the follicular MZ and the red pulp. The perifollicular zone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
167
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(189 citation statements)
references
References 44 publications
(38 reference statements)
11
167
1
2
Order By: Relevance
“…40,50 Further studies have shown that murine FRCs also express CCL19, 15 ERTR7, 51 desmin, and SMA, 40 a reliable marker of myofibroblasts. 42 Although the specific features of this apparatus in human SLOs have been less extensively investigated, 39,52 our observations strongly indicate that CD45 Ϫ , CCL21 ϩ , SMA ϩ fibroblastoid cells, which we have identified in human SLOs, represent FRCs as suggested by their phenotypic marker expression, their dendroid morphology, and their reticular distribution throughout the T area and among the subcapsular sinus and HEVs. The inability to detect CCL21 expression in human SLO SMA ϩ fibroblast cell lines in basal conditions or on in vitro stimulation with tumor necrosis factor-␣ and lymphotoxin, which have been shown to be required for normal expression of CCL21 in mouse spleen, 53 is in keeping with previous reports in murine LN FRCs.…”
Section: Discussionmentioning
confidence: 55%
“…40,50 Further studies have shown that murine FRCs also express CCL19, 15 ERTR7, 51 desmin, and SMA, 40 a reliable marker of myofibroblasts. 42 Although the specific features of this apparatus in human SLOs have been less extensively investigated, 39,52 our observations strongly indicate that CD45 Ϫ , CCL21 ϩ , SMA ϩ fibroblastoid cells, which we have identified in human SLOs, represent FRCs as suggested by their phenotypic marker expression, their dendroid morphology, and their reticular distribution throughout the T area and among the subcapsular sinus and HEVs. The inability to detect CCL21 expression in human SLO SMA ϩ fibroblast cell lines in basal conditions or on in vitro stimulation with tumor necrosis factor-␣ and lymphotoxin, which have been shown to be required for normal expression of CCL21 in mouse spleen, 53 is in keeping with previous reports in murine LN FRCs.…”
Section: Discussionmentioning
confidence: 55%
“…The reticular network must permit great volume changes during an immune response, e.g., associated with the development and regression of germinal centers (Veerman and Vries 1976;Liu et al 1991;Hollowood and Macartney 1992). Accordingly, contractile proteins characteristic of smooth muscle are expressed by reticular cells (Pinkus et al 1986;Toccanier-Pelte et al 1987;Satoh et al 1997Satoh et al ,2009Steiniger et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…SEM of vascular corrosion casts of the human spleen (7) has further confirmed that some of the penicillar arteries, after passing through a splenic follicle, make a hairpin turn and return to the follicle to form bundler arteries. Immunohistochemical studies have focused on the vasculature of the human spleen (11)(12)(13)(14)(15)(16)(17)(18)(19). Steiniger et al performed double staining of serial sections of human spleens for CD34 (a marker for the vascular endothelium) and CD141 (a marker for the sinus en-oxidase activity.…”
mentioning
confidence: 99%